Research progress in BYDV resistance genes derived from wheat and its wild relatives - Zhang, Zengyan; Lin, Zhishan; Xin, Zhiyong (Journal of genetics and genomics, 2009)
Barley yellow dwarf virus （BYDV） may cause a serious disease affecting wheat worldwide. True resistance to BYDV is not naturally found in wheat. BYDV resistance genes are found in more than 10 wild relative species belonging to the genera of Thinopyrum, Agropyron, Elymus, Leymus, Roegneria, and Psathyrostachy. Through wide crosses combining with cell culture, use ofph mutants, or irradiation, 3 BYDV resistance genes in Th. intermedium, including Bdv2, Bdv3 and Bdv4, were introgressed into common wheat background. Various wheat-Th, intermedium addition and substitution, translocation lines with BYDV-resistance were developed and characterized, such as 7D-TAi#1 （bearing Bdv2）, 7B-7Ai#1, 7D-7E （beating Bdv3）, and 2D-2Ai-2 （bearing Bdv4） translocations. Three wheat varieties with BYDV resistance from Th. intermedium were developed and released in Australia and China, respectively. In addition, wheat-Agropyron cristatum translocation lines, wheat-Ag, pulcherrimum addition and substitution lines, and a wheat-Leymus multicaulis addition line （line24） with different resistance genes were developed. Cytological analysis, morphological markers, biochemical markers, and molecular markers associated with the alien chromatin carrying BYDV resistance genes were identified and applied to determine the presence of alien, chromosomes or segments, size of alien chromosome segments, and compositions of the alien chromosomes. Furthermore, some resistance-related genes, such as RGA, P450, HSP70, protein kinases, centrin, and transducin, were identified, which expressed specifically in the resistance translocation lines with Bdv2. These studies lay the foundations for developing resistant wheat cultivars and unraveling the resistance mechanism against BYDV.